Effect Of Nitrite and pH On The Accumulation Of Polyhydroxyalkanoates (PHAs) - Hindwan, Hairiady (Universiti Sains Malaysia, 2018)
Synthetic plastic which is made from fossil fuel is commonly used in human life due to its advantages in term of strength, lightness and durability. Producing plastics from bio-based materials such as polyhydroxyalkanoate (PHA) is one of the method that are able to replace conventional petroleum-derived polymers. However, there are some factors that can affect the accumulation of PHA. The purpose of this study is to investigate the effect of pH and nitrite concentration on the accumulation of PHA. Experiment are conducted for 6 hours operation cycle by using 2 L bioreactors. 1 L sample which consists of PHA-accumulating microorganisms in granules form are taken from 8 L parent reactor and dilute with 1 L water to form mixed liquor. 2 L of mixed liquor are added into the 2 L bioreactor together with the specific concentration of nitrite starting from 30 mg/L, 60 mg/L, 90 mg/L, 120 mg/L and 150 mg/L for each cycles by controlling the value of pH at 7.5. Sample are taken at 0, 0.5, 1.0, 1,5, 2,0, 4.0 and 6.0 h for COD, nitrite (NO2-), FNA, and PHA analysis. Similar step is repeated by changing the pH of the mixed liquor from 6.0, 6.5, 7.0, 7.5 and 8 for each 6 hours cycle without any addition of nitrite. Stock solution of sodium hydroxide, NaOH and acetic acid, CH3COOH were used to control pH value. Accumulation of PHA is observed to be higher at pH of 7.0 and nitrite concentration of 30 mg/L. Effect of nitrite and pH were determined by the presence of free nitrous acid (FNA) in the sample. Hence, the effect of nitrite and pH value on the accumulation of PHA will be determined by the presence of FNA.